Unnoticed Women Architects in the Spanish (South)Eastern Mediterranean Region - Ana Gilsanz-Díaz; Manuel Blanco Lage (Feminismo/s)
This paper reveals the first results of the study carried out within the framework of the research project «A Situated View: Women’s Architecture in Spain from Peripheral Approaches, 1978-2008», in the context of the regions of Valencia and Murcia in Eastern and Southeastern Spain. It deals with the architectural production effectuated exclusively by women architects—alone or together with other women—in the period spanning from 1978 to 2008, i. e., between the democratic transition and the global financial and economic crisis beginning late in 2007. The research brings together bibliographical survey and fieldwork based on direct contact and conversations with women architects, many of whom were absent from the specialised media. Works of different type, use and scale are explored to reveal their increasing production in the last decade of the study, a record of diversity of uses in which residential buildings and works with an average surface area between 1,000 m2 and 10,000 m2 prevail, as well as new buildings as opposed to renovations or refurbishments. This research vindicates the names of women architects, such as Pilar Amorós, Lola Alonso, Lourdes García Sogo, Anna Bofill, and Rufina Campuzano, among other women architects from several generations, and architecture from the Spanish geographic periphery, with the aim of exposing and highlighting a plurality in the ways of making and understanding architecture that completes the historiography. This paper thus consists of a historiographical review open to new contributions and to fill the gaps detected to date.